Bahasa Inggris - Syamsudin, Adi; Desiyanto, Jatim; Ubaidillah, Ubaidillah; Jamaliyah, Imamatul (EDUPEDIA Publisher, 2025)
Character education is very important to build students' personality, especially in the era of globalization which is full of moral problems. At SMKN 1 Omben Sampang, the Khotmil Quran program aims to internalize Islamic values and build students' religious character. To understand the implementation of the program in a vocational school, this research uses qualitative methodology and case studies. Participatory observation, interviews, and documentation studies are the methods used to collect data. The results show that the program helps foster students' characters, especially in terms of discipline, responsibility, and religious awareness. As a result, there are still some issues that need to be addressed. These include uneven student involvement and the need for more organized program management. This program has the potential to be an effective model of Islamic values-based character education in vocational schools by optimizing the implementation strategy and increasing the involvement of all parties.